Additional clothing increases heat load in elite female rugby sevens players - Henderson, M. J.; Chrismas, B. C. R.; Stevens, C. J.; Novak, A.; Fransen, J.; Coutts, A. J.; Taylor, L. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To determine whether elite female rugby sevens players are exposed to core temperatures (Tc) during training in the heat that replicate the temperate match demands previously reported and to investigate whether additional clothing worn during a hot training session meaningfully increases the heat load experienced.